2011
DOI: 10.7322/jhgd.20010
|View full text |Cite
|
Sign up to set email alerts
|

Cognição, motricidade, autocuidados, linguagem e socialização no desenvolvimento de crianças em creche

Abstract: Cognição, motricidade, autocuidados, linguagem Rev Bras Crescimento Desenvolvimento Hum. 2011; 21(2): 220-229 -220 - Resultados: a análise de correlação parcial revelou que ocorreu correlação estatisticamente significante entre os pares de variáveis: cognição x linguagem, socialização x autocuidado e motor x peso/altura e peso/idade. Discussão: percebeu-se a necessidade de implantação de um programa nas creches na área de desenvolvimento infantil, que integre saúde e educação, e que possa ser planejado a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 15 publications
0
8
0
10
Order By: Relevance
“…In the low-income group, inadequacy of tasks involving sustained attention and increased impulsivity, related to the fact that children were unable to sit still during the test, were associated with poor performance on receptive vocabulary and increased externalization behavior. It is worth noting that in two studies (24,28) no statistically significant correlation was found between social behavior and language development. One of these articles (18) shows that the stability of language development was maintained between evaluations, regardless of socioeconomic factors, medical history, maternal intelligence, and gender.…”
Section: Razza Et Al (21)mentioning
confidence: 99%
See 4 more Smart Citations
“…In the low-income group, inadequacy of tasks involving sustained attention and increased impulsivity, related to the fact that children were unable to sit still during the test, were associated with poor performance on receptive vocabulary and increased externalization behavior. It is worth noting that in two studies (24,28) no statistically significant correlation was found between social behavior and language development. One of these articles (18) shows that the stability of language development was maintained between evaluations, regardless of socioeconomic factors, medical history, maternal intelligence, and gender.…”
Section: Razza Et Al (21)mentioning
confidence: 99%
“…Table 2 shows five researches: one clinical trial (18) , three cross-sectional studies (27)(28)(29) , and one qualitative descriptive survey (20) .…”
Section: Analysis Of Selected Studiesmentioning
confidence: 99%
See 3 more Smart Citations